Diffusionless‐Like Transformation Unlocks Pseudocapacitance with Bulk Utilization: Reinventing Fe2O3 in Alkaline Electrolyte. Issue 1 (26th January 2022) - Dong, Taowen; Yi, Wencai; Deng, Ting; Qin, Tingting; Chu, Xianyu; Yang, He; Zheng, Lirong; Yoo, Seung Jo; Kim, Jin‐Gyu; Wang, Zizhun; Wang, Yan; Zhang, Wei; et al.
Abstract : Energy density can be substantially raised and even maximized if the bulk of an electrode material is fully utilized. Transition metal oxides based on conversion reaction mechanism are the imperative choice due to either constructing nanostructure or intercalation pseudocapacitance with their intrinsic limitations. However, the fully bulk utilization of transition metal oxides is hindered by the poor understanding of atomic‐level conversion reaction mechanism, particularly it is largely missing at clarifying how the phase transformation (conversion reaction) determines the electrochemical performance such as power density and cyclic stability. Herein, α‐Fe2 O3 is a case provided to claim how the diffusional and diffusionless transformation determine the electrochemical behaviors, as of its conversion reaction mechanism with fully bulk utilization in alkaline electrolyte. Specifically, the discharge product α‐FeOOH diffusional from Fe(OH)2 is structurally identified as the atomic‐level arch criminal for its cyclic stability deterioration, whereas the counterpart δ‐FeOOH is theoretically diffusionless‐like, unlocking the full potential of the pseudocapacitance with fully bulk utilization. Thus, such pseudocapacitance, in proof‐of‐concept and termed as conversion pseudocapacitance, is achieved via diffusionless‐like transformation. This work not only provides an atomic‐level perspective to reassess the potential electrochemical performance of the transition metal oxides electrode materials based on conversion reaction mechanism but also debuts a new paradigm for pseudocapacitance. Abstract : Fully bulk utilization of electrode materials is one of holy grails for electrochemical energy storage due to its potential to maximize specific capacitance ( C s ). We demonstrate a conversion reaction based on diffusionless transformation, that is, realizing the very fully bulk utilization with excellent stability besides high C s . This is a new model of pseudocapcitance, via the introduction of phase transformation theory into the field of electrochemical energy storage.